Asuhan Kebidanan Komplementer Penanganan Nyeri Pinggang Pada Ibu Hamil Trimester III - Susanti Susanti; Prasida Yunita; Miftahul Jannah (Pusat riset dan Inovasi Nasional, 2024)
Pain is a very common problem in pregnancy, especially in the third trimester of pregnancy. The phenomenon of back pain during pregnancy is one of the most frequently reported complaints among pregnant women, varying from 50% to 70%, based on previous studies in various countries. This study aimed to treat low back pain in the third trimester, in pregnant women, by complementary midwifery care standards. The method used is descriptive, namely describing or describing complementary midwifery care for pregnant women with low back pain problems, with a case study approach. The process of collecting data using direct interviews with patients and families, home visits, performing physical examinations, observing, and making discussions using related journals or books. The results after 3 visits of complementary midwifery care in patients with low back pain (waist) in third-trimester pregnant women resolved the problem and the intervention was stopped. Problems that occur in patients can be resolved and the intervention is stopped.